Socio-economic influence on municipal solid waste generation in Petaling Jaya
Municipal Solid Waste (MSW) generation rate in Malaysia was found to vary according to the tof waste generator, land use and economic level. Waste was collected and sorted from five types of housing area (single-storey terrace, double-storey terrace, single-storey bungalow, double-storey bungalow and condominium) in Section 11 and 12, Petaling Jaya, Selangor Darul Ehsan. Residents in single-store